Status and recent extensions of the Caribou DAQ system for picosecond timing with an FPGA TDC. (1st February 2023) - Buschmann, E.
Abstract: Caribou is a flexible open-source DAQ system developed and used within several collaborative frameworks (CERN EP R&D, RD50, AIDAinnova) for laboratory and high-rate beam tests and easy integration of new silicon-pixel detector prototypes. It uses common hardware, firmware and software components that are shared across different projects, thereby reducing the development effort and cost for such readout systems significantly. This contribution introduces the FASTPIX, APTS and DPTS detectors recently integrated in Caribou and their requirements in terms of waveform sampling and timing of digital pulses. A Time-to-Digital-Converter implemented in the Caribou FPGA was developed to overcome the limitations of the previously used oscilloscope-based readout. It allows for precision timing over large time spans required for the Time-of-Arrival, Time-over-Threshold, and position encoding used in the FASTPIX and DPTS test chips with asynchronous digital readout. A time resolution after calibration of better than 10 ps is achieved.